2017
DOI: 10.1007/s00253-017-8146-3
|View full text |Cite|
|
Sign up to set email alerts
|

Calcium and oxidative stress mediate perillaldehyde-induced apoptosis in Candida albicans

Abstract: New anti-Candida albicans drugs are needed due to the emergence of resistant cases in recent years. Perillaldehyde (PAE) is a natural monoterpenoid compound derived from Perilla frutescens. The minimum inhibitory concentration of PAE against C. albicans was 0.4 μL/mL. We aimed to elucidate the antifungal mode of action of PAE against C. albicans. The antifungal activity of PAE against C. albicans was found to correlate with an elevation in intracellular Ca and accumulation of ROS. Several downstream apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 38 publications
0
42
0
2
Order By: Relevance
“…For a very long time now, PAE has been generally regarded as a safe flavoring ingredient for foods [5], and it has some hygienic functions, such as hypolipidemic action [42], protection against inflammation [43,44], and assisting in curing depression [45]. Besides, in our previous study, PAE showed an effective antifungal activity against some food-borne fungi, such as A. falvus [10], A. niger [9], and Ceratocystis fimbriata [46], with a striking inhibition of food decay, and against Candida albicans, which protects humans from candidiasis infection [44,47]. Moreover, the antifungal pathways of PAE must be partly explained.…”
Section: Discussionmentioning
confidence: 94%
“…For a very long time now, PAE has been generally regarded as a safe flavoring ingredient for foods [5], and it has some hygienic functions, such as hypolipidemic action [42], protection against inflammation [43,44], and assisting in curing depression [45]. Besides, in our previous study, PAE showed an effective antifungal activity against some food-borne fungi, such as A. falvus [10], A. niger [9], and Ceratocystis fimbriata [46], with a striking inhibition of food decay, and against Candida albicans, which protects humans from candidiasis infection [44,47]. Moreover, the antifungal pathways of PAE must be partly explained.…”
Section: Discussionmentioning
confidence: 94%
“…We examined the apoptotic characteristics of CA-treated cells, and the results showed that CA caused the externalization of PS on the outer surface of the plasma membrane (Figure 7). DNA damage and nuclear fragmentation are typical morphological features of apoptotic cells in the late stage of apoptosis (Tian et al, 2017). It is well-known that DAPI fluorescent probes are used to detect chromatin condensation, and TUNEL staining is one of the most reliable strategies for identifying the amount of DNA fragmentation visible.…”
Section: Discussionmentioning
confidence: 99%
“…Broth microdilution methods are commonly used for in vitro antifungal assays (Tian et al, 2017). For our experiments, 80 µl of different concentrations of CA, 100 µl of potato dextrose broth (PDB), and 20 µl 5 × 10 6 spores/ml A. flavus were added to each of 10 wells.…”
Section: Antifungal Susceptibility Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…During apoptosis, several hallmarks, such as DNA fragmentation, cell cycle arrest, and caspase activation, are evident . Both caspase activation and DNA fragmentation were observed in the silymarin‐treated and DIDS‐pretreated cells, but not in the TEA‐pretreated cells.…”
Section: Discussionmentioning
confidence: 99%